2013
DOI: 10.4103/2277-9531.112684
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of nutrition education program based on health belief model compared with traditional training

Abstract: Introduction:This study was aimed to compare the effect of nutrition educational program based on HBM with traditional education recommended weight gain among pregnant women in Gonabad. Target population was pregnant women who were resided in Gonabad and went to urban health care centers for prenatal cares.Materials and Methods:110 pregnant women (case group: 54, control group: 56) were selected who had come to this centers in the first stage of prenatal care (6th -10th week of pregnancy) in 1388 and were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 9 publications
4
27
0
1
Order By: Relevance
“…HBM has been applied widely and studied extensively since its introduction, and several systemic review and meta-analyses have reported on its effectiveness in predicting and explaining healthrelated behavior (Carpenter, 2010;Jones, Smith, & Llewellyn, 2014). HBM has specifically been applied to perinatal issues such as contraception use (Hall, 2012), dietary behaviors and gestational weight gain during pregnancy (Khoramabadi et al, 2015;Ledoux et al, 2017;Sharifirad et al, 2013), and pregnant women's decisions regarding mode of delivery (Loke, Davies, & Li, 2015). Izadirad, Niknami, Zareban, and Hidarnia (2017) used the HBM tenets of perceived benefits, barriers, and threats to design a program to improve uptake of prenatal care services among Iranian women.…”
Section: Introductionmentioning
confidence: 99%
“…HBM has been applied widely and studied extensively since its introduction, and several systemic review and meta-analyses have reported on its effectiveness in predicting and explaining healthrelated behavior (Carpenter, 2010;Jones, Smith, & Llewellyn, 2014). HBM has specifically been applied to perinatal issues such as contraception use (Hall, 2012), dietary behaviors and gestational weight gain during pregnancy (Khoramabadi et al, 2015;Ledoux et al, 2017;Sharifirad et al, 2013), and pregnant women's decisions regarding mode of delivery (Loke, Davies, & Li, 2015). Izadirad, Niknami, Zareban, and Hidarnia (2017) used the HBM tenets of perceived benefits, barriers, and threats to design a program to improve uptake of prenatal care services among Iranian women.…”
Section: Introductionmentioning
confidence: 99%
“…In previous evidence, it was focused that higher levels of self-efficacy contributed to physical activity and lower dietary ( 15 ). Previous studies showed that health belief model is a useful framework for describing the healthy nutrition behavior ( 16 - 19 ). Moreover, this model has been used in risk reduction of cardiovascular disease in college students ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the health belief theories demonstrated that individuals with low perceived susceptibility deny the possibility of suffering from a health condition or disease, those with average perceived susceptibility consider themselves susceptible to a health condition, and those with high perceived susceptibility perceive the real risk of suffering from a health condition [ 23 ]. Some studies showed the effect of educational interventions on increasing perceived susceptibility to dietary behaviors among pregnant women [ 24 , 25 ]. Considering the hypothesis of the present study individuals’ perceived susceptibility could be increased by designing and implementing educational interventions.…”
Section: Discussionmentioning
confidence: 99%